Personalized electro-acupuncture versus auricular-acupuncture comparative effectiveness (PEACE): A protocol of a randomized controlled trial for chronic musculoskeletal pain in cancer survivors. Issue 21 (22nd May 2020) - Liou, Kevin T.; Baser, Ray; Romero, Sally A.D.; Green, Jamie; Li, Q. Susan; Orlow, Irene; Panageas, Katherine S.; Mao, Jun J.
Abstract: Introduction: Chronic pain is a leading cause of disability and remains under-treated in nearly half of patients with cancer. The opioid crisis has highlighted an urgent public health need for effective nonpharmacological pain management. Electroacupuncture (EA) and Battlefield Acupuncture (BFA) represent nonpharmacological modalities used in clinical practice to manage pain; however, their effectiveness has not been rigorously evaluated in oncology settings. Methods: We describe the design of a 3-arm, parallel, single-center, multisite randomized controlled trial that investigates EA and BFA versus usual-care wait-list control (WLC) for chronic musculoskeletal pain among 360 patients with diverse cancer types across various stages. The primary aim is to compare effects of EA and BFA versus WLC on pain, physical function, and co-morbid symptoms. The secondary aim is to examine the interaction between patient outcome expectancy and acupuncture modality (EA vs BFA) on pain reduction. The tertiary aim is to evaluate the association between genetic polymorphisms and responses to acupuncture. Patients will be randomized in a 2:2:1 ratio to EA:BFA:WLC. Acupuncture groups will receive weekly treatments over 10 weeks. WLC will receive usual care over the same evaluation period as the acupuncture groups. The primary endpoint will be the change in average pain intensity score from baseline to week 12. We will collect validated patient-reported outcomes and blood/saliva samples at multiple timepoints over 24 weeks. Discussion: Our findings will advance nonpharmacological pain management in oncology and inform personalized treatment approaches that integrate individuals' expectations and genetic biomarkers to deliver "precision" acupuncture to cancer patients with chronic pain. Trial Registration: ClinicalTrials.gov Identifier: NCT02979574